2014
DOI: 10.1017/s002185961400077x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of the gestation period for welfare of lambs: maternal stressors and lamb vigour and wellbeing

Abstract: The prenatal period is of critical importance in defining how individuals respond to their environment throughout life. Stress experienced by pregnant females has been shown to have detrimental effects on offspring behaviour, health and productivity. The sheep has been used extensively as a model species to inform human studies. However, in the farmed environment, the consequences for the lamb of the imposition of prenatal stresses upon the ewe have received much less attention. The stressors that pregnant ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 99 publications
4
23
0
Order By: Relevance
“…However, the extent to which UN influences mortality through each of these routes has not been thoroughly investigated. Rooke et al (2015) found, across all studies reviewed, that UN consistently reduced birthweight only in the last third of ovine pregnancy with the reduction in birthweight being related both to the length and severity of UN. In the first two-thirds of pregnancy, UN only reduced birthweight in specific circumstances.…”
Section: Biological Factors Involved In Lamb and Kid Mortality/survivalmentioning
confidence: 86%
See 2 more Smart Citations
“…However, the extent to which UN influences mortality through each of these routes has not been thoroughly investigated. Rooke et al (2015) found, across all studies reviewed, that UN consistently reduced birthweight only in the last third of ovine pregnancy with the reduction in birthweight being related both to the length and severity of UN. In the first two-thirds of pregnancy, UN only reduced birthweight in specific circumstances.…”
Section: Biological Factors Involved In Lamb and Kid Mortality/survivalmentioning
confidence: 86%
“…Extensive research (see recent reviews for individual studies; Kenyon and Blair, 2014;Rooke et al, 2015) has described how changes in nutrition, both total and specific nutrient supply, impact on neonatal lamb characteristics relevant to survival. As, in temperate regions, the ewe is a seasonal breeder, and pregnancy in these climatic zones coincides with winter when nutrient availability from grazing is limited, an annual cycle approach to feeding the ewe has long been advised (Russell, 1985; Figure 3).…”
Section: Biological Factors Involved In Lamb and Kid Mortality/survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies consistently show that maternal undernutrition of the ewe in late pregnancy (after Day 100) reduces lamb birthweight (for a review, see Rooke et al 2015). Undernutrition before Day 100 has variable effects across different studies: severe early undernutrition has a marked effect on birthweight and mortality (Vincent et al 1985); and moderate undernutrition in early to mid-gestation generally does not affect birthweight, except in young and growing females (Munoz et al 2009) or ewes selected or adapted for a well-fed environment (Burt et al 2007;Rooke et al 2010).…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%
“…Arnott et al (2012) employed the systematic review process advocated by Sargeant et al (2006) to minimize systematic and random errors in study selection. Previously, we (Rooke et al 2015) applied the approach of Arnott et al (2012) and identified stressors applied to the ewe during gestation which were practically relevant. In Rooke et al (2015), the subject material was limited (because of the large number of studies)…”
Section: Introductionmentioning
confidence: 99%